Optimizing the Local Potential of Coffee Aromatherapy Candles as a Flagship Product of Sekolah Alam Nusantara in Suci Villages - Mayla Syifani Zulfa; Nadilatus Salsabila; Bagas Permana Putra; Lailatul Qomariah; Siti Shofa Assyifa'ul Qulbi Barid; Sri Wahyuni (Yayasan Keluarga Guru Mandiri, 2025)
Suci Village, located in the Panti District of Jember Regency, boasts an abundance of coffee potential that has largely been underutilized for commercial purposes. To increase its added value and empower the local community, the Community Partnership Program (PKM) introduced a training program for producing coffee-based aromatherapy candles at Sekolah Alam Nusantara. The program employed a participatory approach, involving 20 participants, primarily homemakers, and consisted of three stages: material delivery, hands-on practice, and evaluation. Pre- and post-tests were used to evaluate knowledge improvement. The results demonstrated a substantial increase in community knowledge and skills. Before the training, only 25% of the participants were familiar with aromatherapy candles. After the program, however, all of the participants understood their benefits and basic production techniques. The candles produced exhibited a distinctive coffee aroma, functional value, and potential to become environmentally friendly, flagship products of Suci Village. This initiative strengthened the community's capacity to utilize natural resources, encouraged creative entrepreneurship, and supported circular economy practices. This study contributes to the literature on community empowerment by demonstrating how local commodities, such as coffee, can be transformed into valuable products. Furthermore, the study provides a replicable model for sustainable rural development through skill-based training and product innovation.